Determinan Perilaku Menabung di Kalangan Mahasiswa Perguruan Tinggi di Indonesia - Isabella Magdalena Simbolon; Mahda Aidil Hanafi; Melani Simanjuntak (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Student savings behavior is an important indicator in the formation of financial independence and long-term economic readiness among the younger generation. This study aims to examine the determinants of college students' saving behavior in Indonesia by analyzing the role of financial literacy, self-control, social environment, family economic conditions, and the influence of financial digitalization. The research method used is a qualitative approach through a literature study by systematically analyzing various accredited national journal articles, scientific proceedings, and relevant institutional publications. The results and discussion show that financial literacy is a fundamental factor that shapes students' understanding and attitudes towards financial management, while self-control functions as an internal mechanism that maintains consistency in saving behavior amid consumptive pressures and peer influence. Family and social environments also play a role in shaping students' financial habits, while financial digitalization presents opportunities and challenges depending on individuals' literacy and self-control capacities. This study concludes that students' saving behavior is influenced by the multidimensional interaction between cognitive, psychological, social, and structural factors.